Pembersihan Hati dalam Tafsir Sufi Isharī berkaitan Pendidikan Integriti Individu - Mahyuddin Hashim; Abdul Rahim Zumrah; Mazlan Ibrahim; Zamrie Ibrahim @ Musa; Ahmad Yussuf; Nursyahirah Wahidah Masrom (Universiti Sains Islam Malaysia, 2026)
Journal of Maʿālim Al-Qurʾān Wa Al-Sunnah, Volume 21 Issue 2 Page (1–25)